Can somatotype influence the static postural control? A new proposal of investigation - Penna, G.; Zecca, G.; Altavilla, G.; D`Isanto, T.; Russo, L. (Journal of Human Sport & Exercise, 2023)
Static postural control can be influenced by several aspects, even anthropometric parameters or somatotypes. The aim of this research was to identify the influence of the somatotype on the static postural control and the association between the somatotype and the sagittal posture alignment. Eighty-three subjects (n = 83) were included in the study and were tested for somatotypes, postural sway control and static sagittal postural alignment. The mesomorphs showed a body mass and a BMI significantly higher than the other somatotypes (p < .0001); the ectomorphs have shown a postural sway significantly higher than the mesomorphs (p = .028). An association between the somatotype and the sagittal posture (p = .027) was also measured. The data of this research are partly consistent with previous literature about somatotypes and postural control but data on the postural sagittal alignment offer an innovative perspective. In conclusion, an interaction between somatotypes, sagittal postural alignment and postural sway control is present and health professionals should consider it.